2013
DOI: 10.1007/s10549-013-2426-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of key oestrogen-regulated genes differs substantially across the menstrual cycle in oestrogen receptor-positive primary breast cancer

Abstract: Plasma estradiol (E2) and progesterone vary markedly through the menstrual cycle. Data on whether these differences in hormone levels affect gene expression in oestrogen receptor-positive (ER+) tumours are inconsistent. We wished to determine whether there are substantial changes in the expression of oestrogen-regulated genes (ERGs) in ER+ breast cancer through the menstrual cycle. One hundred and seventy five paraffin-embedded ER+ breast carcinomas from premenopausal patients were analysed. Timing of the ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 25 publications
5
32
1
Order By: Relevance
“…TFF1, originally known as pS2, was the gene which correlated most significantly with plasma estradiol concentration in postmenopausal ER-positive breast cancer tissues [13]. It was also reported that expression levels of TFF1, similar to PgR, in ER-positive breast tumors differed across the menstrual cycle in premenopausal women, although expression of proliferation genes, such as Ki67, did not differ during the cycle [12].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…TFF1, originally known as pS2, was the gene which correlated most significantly with plasma estradiol concentration in postmenopausal ER-positive breast cancer tissues [13]. It was also reported that expression levels of TFF1, similar to PgR, in ER-positive breast tumors differed across the menstrual cycle in premenopausal women, although expression of proliferation genes, such as Ki67, did not differ during the cycle [12].…”
Section: Discussionmentioning
confidence: 93%
“…We previously analyzed genetic and environmental predictors, endogenous hormones and growth factors, and risk of ER-positive breast cancer, and demonstrated that risk factors differed between women of different menopausal status [24]. It has been reported that plasma estradiol levels are significantly associated with estrogen-responsive gene expression of ER-positive breast cancers in both pre-and postmenopausal women [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating levels of estradiol in blood of premenopausal women change between 100 to 700 pmol/L within a month (57), resulting in the alternating expression of estrogen-regulated proteins in tissues, blood and urine (58). Because estrogenregulated proteins are often identified as disease biomarkers (59), dynamic profile of such proteins in biological fluids may eliminate some false biomarkers (60).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that GREB1 levels in breast tumors correlate with both plasma and serum E2 levels in premenopausal women [40][41][42]. Quantitative RT-PCR showed that GREB1 and three other known ESR1-regulated genes (TFF1, PGR, PDZK1) changed throughout the menstrual cycle in ESR1+ but not ESR1-tumors [42].…”
Section: Other Factors Regulating Greb1 Expressionmentioning
confidence: 97%